Agreement of the Serum Spec fPL™ and 1, 2‐O‐Dilauryl‐Rac‐Glycero‐3‐Glutaric Acid‐(6′‐Methylresorufin) Ester Lipase Assay for the Determination of Serum Lipase in Cats with Suspicion of Pancreatitis. (26th July 2013) - Oppliger, S.; Hartnack, S.; Riond, B.; Reusch, C.E.; Kook, P.H.
<x xml:space="preserve">Abstract</x> Background Serum lipase activities measured by catalytic assays are claimed to be of limited utility for diagnosing pancreatitis in cats. The Spec fPL assay currently is believed the most sensitive test; however, studies comparing different lipase assays are lacking. 1, 2‐o‐dilauryl‐rac‐glycero‐3‐glutaric acid‐(6′‐methylresorufin) ester (DGGR) assay for the determination of lipase activity has been evaluated in dogs, but no information is available in cats. Objectives To investigate the agreement of DGGR‐lipase activity and Spec fPL concentration in cats with clinical signs consistent with pancreatitis. Animals Two hundred fifty‐one client‐owned cats. Methods DGGR‐lipase activity and Spec fPL concentration measured from the same blood sample in cats undergoing investigation for pancreatitis. The agreement between DGGR‐lipase and Spec fPL at different cutoffs was assessed using Cohen's kappa coefficient (κ). Sensitivity and specificity were calculated for 31 cases where pancreatic histopathology was available. Results DGGR‐lipase (cutoff, 26 U/L) and Spec fPL (cutoff, >5.3 μg/L) had a κ of 0.68 (standard error [SE] 0.046). DGGR‐lipase (cutoff, 26 U/L) and Spec fPL (cutoff, >3.5 μg/L) had a κ of 0.60 (SE, 0.05). The maximum κ at a Spec fPL cutoff >5.3 μg/L was found when the DGGR‐lipase cutoff was set >34 U/L and calculated as 0.755 (SE, 0.042). Sensitivity and specificity were 48% and 63% for DGGR‐lipase (cut‐off, 26 U/L) and 57% and 63% for Spec fPL (>5.3 μg/L), respectively. Conclusions and Clinical Importance Both lipase assays agreed substantially. DGGR assay seems a useful and cost‐efficient method compared to the Spec fPL test.